Development of pre-seeded tissue-engineered vascular grafts in vitro - M. Yu. Khanova; L. V. Antonova (Фундаментальная и клиническая медицина)
Current vascular surgery employs reconstruction of occluded blood vessels using autologous grafts. As a considerable proportion of patients lack healthy autologous vessels to be used as the grafts, the development of tissue-engineered, small-diameter vascular grafts has significant clinical relevance. Biodegradable vascular grafts, which have a defined degradation rate upon the implantation, provide an opportunity for the controlled vascular regeneration. Such polymer framework acts as a guiding matrix for organising the patient's newly formed tissues to ensure consistent and complete vessel remodeling. The crucial aspect of tissue-engineered vascular graft regeneration is endothelialisation, as non-endothelialised blood vessels suffer from the thrombosis if having < 5 mm diameter because of low blood flow. This review describes two approaches to stimulate endothelialization. The first is the biofunctionalization of the luminal surface with the bioactive peptides with the following in situ implantation. Using the body as a bioreactor, this approach relies on the selective recruitment of endothelial cells. The second approach includes in vitro pre-seeding of a luminal surface with an endothelial cell monolayer. The development of such pre-seeded vascular grafts requires the choice of an appropriate polymer for the manufacture of a 3D matrix, isolation of endothelial cell culture, and tuning of mechanical stimuli to control the cell specification during the pre-seeding. In addition to the pre-seeding of endothelial cells on the luminal surface, it is necessary to adapt them to the flow to prevent shedding or incorrect orientation. Cell adhesion can be enhanced by the attachment of extracellular matrix proteins to the luminal surface or by mimicking natural blood flow conditions. Sustained mechanical stimuli facilitate the adaptation of endothelial cells to the flow and contribute to the maturation of endothelial progenitor cells.